The Effectiveness of Psychoreligius Therapy on Sleep Quality and Anxiety in Diabetes Mellitus Patientstype 2 - Fendy Valentino Fauzan Aftina; Sri Poeranto; Yulian Wiji Utami (GoAcademica Research & Publishing, 2021)
Diabetes mellitus is a chronic degenerative disease characterized by an increase in glucose levels in the blood. Anxiety and sleep quality disturbances are problems that are often experienced by people with diabetes mellitus due to prolonged stressors. The purpose of this study was to determine the effectiveness of psychoreligious therapy on anxiety scores and sleep quality scores in type 2 diabetes mellitus patients in the Junrejo Health Center, Batu City. This study used a queasy experimental design with a pretest and posttest control group design. The number of samples was 36 respondents who were divided into the experimental group (psychoreligious therapy) and the control group (health education) each of 18 respondents. The sample selection used purposive sampling. The results of this study indicate that psychoreligious therapy has ρ value < 0.05, which means that there is a significant difference between the difference in anxiety scores and the difference in sleep quality scores before and after being given psychoreligious therapy, so the alternative hypothesis is accepted and the null hypothesis is rejected. This study concludes that psychoreligious therapy is more effective than health education on anxiety and sleep quality in patients with type 2 diabetes mellitus.